The athlete's hematological response to hypoxia: A meta‐analysis on the influence of altitude exposure on key biomarkers of erythropoiesis. Issue 1 (31st October 2017) - Lobigs, Louisa M.; Sharpe, Ken; Garvican‐Lewis, Laura A.; Gore, Christopher J.; Peeling, Peter; Dawson, Brian; Schumacher, Yorck O.
Abstract: Altitude training is associated with changes in blood markers, which can confound results of the Athlete?s Biological Passport (ABP). This meta‐analysis aims to describe the fluctuations during‐ and post‐altitude in key ABP variables; hemoglobin concentration ([Hb]), square‐root transformed reticulocyte percentage (sqrt(retic%)) and the OFF‐score. Individual de‐identified raw data were provided from 17 studies. Separate linear mixed effects analyses were performed for delta values from baseline for [Hb], sqrt(retic%) and OFF‐score, by altitude phase (during and post). Mixed models were fitted with the hierarchical structure: study and subject within study as random effects. Delta values as response variables and altitude dose (in kilometer hours; km.hr = altitude (m) / 1000 x hours), sex, age, protocol and baseline values as fixed effects. Allowances were made for potential autocorrelation. Within two days at natural altitude [Hb] rapidly increased. Subsequent delta [Hb] values increased with altitude dose, reaching a plateau of 0.94 g/dL [95%CI (0.69, 1.20)] at 1000 km.hr. Delta sqrt(retic%) and OFF‐score were the first to identify an erythrocyte response, with respective increases and decreases observed within 100 to 200 km.hr. Post‐altitude, [Hb] remained elevated for two weeks. Delta sqrt(retic%) declined below baseline, the magnitude of change was dependent on altitude dose. Baseline values were a significant covariate (p<0.05). The response to altitude is complex resulting in a wide range of individual responses, influenced primarily by altitude dose and baseline values. Improved knowledge of the plausible hematological variations during‐ and post‐altitude provides fundamental information for both the ABP expert and sports physician.